Osteoarticular Infections Caused by Erysipelothrix rhusiopathiae: Case Report and Literature Review. (8th October 2021) - Maillard, Alexis; Wakim, Yara; Itani, Oula; Ousser, Fateh; Bleibtreu, Alexandre; Caumes, Eric; Monsel, Gentiane
Abstract: We present a case of Erysipelothrix rhusiopathiae spondylodiscitis in an otherwise healthy man, occurring 1 year after exposure. The patient was cured after 6 weeks of treatment with amoxicillin followed by ciprofloxacin without surgery. Erysipelothrix rhusiopathiae can cause severe osteoarticular infections with a delayed presentation following exposure to the pathogen.